Major Baltic Inflow Statistics – Revised - Mohrholz, Volker (Frontiers in Marine Science, 2018)
Major Baltic inflow events (MBI) transport large amounts of saline water into the Baltic. They are the solely source for deep water ventilation in the central Baltic basins, and control to a large extent the environmental conditions below the permanent halocline. Available series of MBI frequency and intensity depict strong decrease of MBI frequency after the 1980ies, followed by long lasting stagnation periods in the central Baltic basins. However, the expected decrease in mean salinity of the Baltic was not observed. Also the frequency of large volume changes of the Baltic has not changed, and recent model studies predict a slight increase of MBI frequency with warming climate. Using long term data series of sea level, river discharge, and salinity from the Belt Sea and the Sound a continuous series of barotropic inflows was reconstructed for the period from 1887 till present. A comparison with the MBI series of Fischer and Matthäus (1996) revealed significant differences in the period since the 1980ies. The reasons for the deviations are mainly the lack of appropriate data between 1976 and 1991, and the change in observation methods afterwards, which caused a bias in the inflow statistics. In contrast to earlier investigations the revised MBI series depicts no significant long term trend in MBI frequency and intensity, contradicting the hypothesis that climate change caused a decreasing MBI frequency. There exists a decadal variability of MBI with a main period of 25 to 30 years. Periods with reduced MBI frequency were identified. The revised MBI series was proved with observations of dissolved oxygen and salinity in the bottom layer of the Bornholm basin. Until today climate change has no obvious impact on the MBI related oxygen supply to the central Baltic Sea. The increased eutrophication during the last century is most probably the main driver for temporal and spatial spreading of suboxic and anoxic conditions in the deep layer of the Baltic Sea.